Analisis Perubahan Perilaku dan Usaha Dalam Kaji Terap Good Farming Practices dan Aplikasi Sidik di Kecamatan Panjalu Kabupaten Ciamis - Aldi Prayoga; Wardani; Arif Nindyo Kisworo (Politeknik Pembangunan Pertanian Bogor, 2022)
The supply of beef cattle and beef in the country has been based on smallholder farms around 97.7%. The growth of domestic beef production (supply) during 2005-2013 continues to increase, but has not been able to keep up with the pace of demand so imports are needed. Therefore, it is necessary to have an intensive beef cattle maintenance system through good beef cattle fattening agribusiness (good farming practice). Based on this background, the objectives to be achieved are: 1). Identify the level of change in knowledge, attitudes and skills of farmers. 2). To identify the effect of using the Animal Husbandry SIDIK application in beef cattle maintenance management on the income of farmers. The research method used is the interview method through a structured questionnaire from 30 respondents. The data analysis method used extension analysis (Padmowihardjo formula, 1999), and business analysis (calculation of income level). The applied study was carried out for 40 days at the Gentra Pusaka Tunas Muda Farmer Group, which consisted of 3 treatments, namely control (P0) of traditional cattle fattening. The second treatment (P1) was fattening cattle with GFP. While the third treatment (P2) is that farmers apply GFP + Livestock Imprint Application. Evaluation of the implementation of the extension obtained the results: There was a change in knowledge of (39.58% = quite successful), skills (37.39% = quite successful), and attitudes (41.39% = quite successful). Business analysis obtained results P0 = Rp.1.214.400.00, P1 = Rp.1.376.600.00, and P2 = Rp.1.571.000,00. It can be concluded that the application of GFP and Livestock Print Applications can be recommended for beef cattle fattening efforts.